Effectiveness of a lifestyle exercise program for older people receiving a restorative home care service: study protocol for a pragmatic randomised controlled trial - Burton, Elissa; Lewin, Gill; Clemson, L.; Boldy, Duncan (BioMed Central, 2013)
BACKGROUND: Restorative home care services help older people maximise their independence using a multidimensional approach. They usually include an exercise program designed to improve the older person’s strength, balance and function. The types of programs currently offered require allocation of time during the day to complete specific exercises. This is not how the majority of home care clients prefer to be active and may be one of the reasons that few older people do the exercises regularly and continue the exercises post discharge. This paper describes the study protocol to test whether a Lifestyle Functional Exercise (LiFE) program: 1) is undertaken more often; 2) is more likely to be continued over the longer term; and, 3) will result in greater functional gains compared to a standard exercise program for older people receiving a restorative home care service.METHODS/DESIGN: Design: A pragmatic randomised controlled trial (RCT) design was employed with two study arms: LiFE program (intervention) and the current exercise program (control). Setting: Silver Chain, a health and community care organisation in Perth, Western Australia. Participants: One hundred and fifty restorative home care clients, aged 65 years and older. Measurements: The primary outcome is a composite measure incorporating balance, strength and mobility. Other outcome measures include: physical functioning, falls efficacy, and levels of disability and functioning.DISCUSSION: If LiFE is more effective than the current exercise program, the evidence will be presented to the service management accompanied by the recommendation that it be adopted as the generic exercise program to be used within the restorative home care service.